2010
DOI: 10.1007/s00284-010-9811-2
|View full text |Cite
|
Sign up to set email alerts
|

Extremely High Frequency Electromagnetic Irradiation in Combination with Antibiotics Enhances Antibacterial Effects on Escherichia coli

Abstract: Antibacterial effects of the electromagnetic irradiation (EMI) of 51.8 and 53 GHz frequencies with low intensity (the flux capacity of 0.06 mW/cm(2)) and non-thermal action were investigated upon direct irradiation of E. coli K12. Significant decrease in bacterial growth rate and in the number of viable cells, marked change in H(+) and K(+) transport across membrane were shown. Subsequent addition of kanamycin or ceftriaxone (15 or 0.4 μM, respectively) enhanced the effects of irradiation. This was maximally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…However, for Wi-Fi exposure, this significant change was observed at 4.5 hours and for the RF simulator at the 12 th hour. Many studies have demonstrated that the bacterial response to electromagnetic fields is dependent on several factors including: intensity, frequency, duration of exposure, and other physicochemical properties of the fields (22,37,38). As mentioned, the frequency of Wi-Fi router was 2.4 GHz and RF simulator was 900 MHz, maximum bacterial response to this radiation occurred at different times, which was related to their frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for Wi-Fi exposure, this significant change was observed at 4.5 hours and for the RF simulator at the 12 th hour. Many studies have demonstrated that the bacterial response to electromagnetic fields is dependent on several factors including: intensity, frequency, duration of exposure, and other physicochemical properties of the fields (22,37,38). As mentioned, the frequency of Wi-Fi router was 2.4 GHz and RF simulator was 900 MHz, maximum bacterial response to this radiation occurred at different times, which was related to their frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial resistance to one or more antibiotics occurs by various mechanisms (24)(25)(26). In this way, EMFs as an environmental agent could influence cellular responses such as antimicrobial susceptibility through different pathways (4,20,22,23,27). The aim of the present study was to evaluate the antimicrobial susceptibility of K. pneumoniae under 900 MHz radiofrequency radiations condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in cell membrane properties such as bioenergetics, transport and enzyme activity by extremely high‐frequency EMI (Trchounian et al ., ; Tadevosyan et al ., ; Torgomyan et al ., ) might serve as a molecular cellular basis for EMI effects on bacteria, and confirm the membranotropic mechanism of the action of EMI. The H + ‐translocating F 0 F 1 ‐ATPase, which is the main membrane bioenergetic component, is among probable targets of EMI (Tadevosyan et al ., ; Tadevosyan & Trchounian, ; Torgomyan et al ., , b).…”
Section: Introductionmentioning
confidence: 64%
“…Previous studies in our laboratory have demonstrated that coherent extremely high frequency EMI decreases the growth rate of Enterococcus hirae (Ohanyan et al ., ) and Escherichia coli (Trchounian et al ., ; Tadevosyan et al ., , ; Torgomyan & Trchounian, ; Torgomyan et al ., , b). Antibacterial effects depend on the intensity of irradiation, exposure duration, the phase and conditions of bacterial growth, the composition and pH of the growth medium, and characteristics of the bacterial strains.…”
Section: Introductionmentioning
confidence: 99%